Using And Interacting On An Online Narrative Writing Platform: An Exploratory Study - Annamalai, A. Nagaletchimee (2013)
The advent and the continued development of the Internet has given birth to a plethora of online writing apps, softwares and platforms that provide an opportunity for educators and students alike to develop and enhance their writing skill online. The main aim of this exploratory study is to investigate how the use of an online narrative writing platform as defined in this study enhances students’ narrative writing. The study also investigates the patterns of interactions in a collaborative learning environment and the participants’ experiences and reflections in the use of the online narrative writing platform. The study explores the use of the online narrative writing platform in a specific setting of six students and a teacher in a Chinese Secondary school in Penang. The data sources of this qualitative exploratory study are written assignments, online interactions, interviews and reflections. Qualitative data analysis procedures include stages of data preparation and organisation, data reduction into themes through coding processes and final representation of findings. The multiple sources of data enabled data triangulation process to be carried out. The findings revealed that the students improved their narrative writing ability after engaging in the online narrative writing platform. The patterns of interactions were analysed according to cognitive, teaching and social presences. The social presence showed the teacher and the students were constantly acknowledging and caring for one another. For teaching presence, the teacher played a major role as the subject matter expert and in directing the students’ attention to important aspects of the task. The cognitive presence, showed that students and teacher are giving and receiving comments to contribute to thinking and learning. An additional presence related to social presence was identified. This is termed as social learning presence.